Immunogenicity and efficiency of a 23-valent pneumococcal vaccine in patients with rheumatoid arthritis: results of a 5-year follow up study - D. V. Bukhanova; M. S. Sergeeva; B. S. Belov; G. M. Tarasova; M. V. Cherkasova; Yu. A. Muraviev; G. V. Lukina; N. V. Demidova (Современная ревматология)
Objective: to study the efficacy, immunogenicity, and safety of a 23-valent pneumococcal polysaccharide vaccine (PPSV-23) in patients with rheumatoid arthritis (RA) receiving disease-modifying antirheumatic drugs (DMARDs) and biologic agents (BAs) during a 5-year follow-up.Patients and methods. The investigation included 79 RA patients with a recent history of ≥2 episodes of lower respiratory tract infections (bronchitis, pneumonia). A single dose (0.5 ml) of PPSV-23 was administered subcutaneously during continued methotrexate/leflunomide therapy or 28–30 days before using TNF-α inhibitors. All the patients were followed up during the first year; 39 patients at 24 months (Visit 5), 13 at 36 months (Visit 6), 23 at 48 months (Visit 7), and 18 at 60 months (Visit 8).Results and discussion. RA patients receiving various therapies were noted to have a marked positive immune response to PPSV-23, which was manifested by a significant increase in the postimmunization response coefficient. Vaccination responses were recorded in 61% of the patients with RA. The level of postvaccination responses tended to decrease at the 4-year follow-up. Only one case of community-acquired pneumonia of unknown etiology was detected at 5 years of follow-up.Conclusion. The data obtained by the authors for the first time in the 5-year prospective study indicate the sufficient and long-term immunogenicity, high efficacy, and safety of PPSV-23 in RA patients treated with DMARDs and BAs. Further clinical trials are needed to clarify the influence of various factors on the efficacy and immunogenicity of PPSV-23 and on the degree of their correlation in patients with RA.Objective: to study the efficacy, immunogenicity, and safety of a 23-valent pneumococcal polysaccharide vaccine (PPSV-23) in patients with rheumatoid arthritis (RA) receiving disease-modifying antirheumatic drugs (DMARDs) and biologic agents (BAs) during a 5-year follow-up.Patients and methods. The investigation included 79 RA patients with a recent history of ≥2 episodes of lower respiratory tract infections (bronchitis, pneumonia). A single dose (0.5 ml) of PPSV-23 was administered subcutaneously during continued methotrexate/leflunomide therapy or 28–30 days before using TNF-α inhibitors. All the patients were followed up during the first year; 39 patients at 24 months (Visit 5), 13 at 36 months (Visit 6), 23 at 48 months (Visit 7), and 18 at 60 months (Visit 8).Results and discussion. RA patients receiving various therapies were noted to have a marked positive immune response to PPSV-23, which was manifested by a significant increase in the postimmunization response coefficient. Vaccination responses were recorded in 61% of the patients with RA. The level of postvaccination responses tended to decrease at the 4-year follow-up. Only one case of community-acquired pneumonia of unknown etiology was detected at 5 years of follow-up.Conclusion. The data obtained by the authors for the first time in the 5-year prospective study indicate the sufficient and long-term immunogenicity, high efficacy, and safety of PPSV-23 in RA patients treated with DMARDs and BAs. Further clinical trials are needed to clarify the influence of various factors on the efficacy and immunogenicity of PPSV-23 and on the degree of their correlation in patients with RA.